2022
DOI: 10.55730/1300-0527.3469
|View full text |Cite
|
Sign up to set email alerts
|

Study of silanized nanostructures with immobilized fumarase for production of L-malate

Abstract: The conversion of fumaric acid into L-malate by fumarase immobilized on silanized nanostructures was analyzed experimentally. The enzyme was bound to the silanized nanostructures. We carried out scanning electron microscopy (SEM), fourier transform infrared spectroscopy (FTIR) analysis, zeta size analysis and surface area calculation for the characterization of the nanostructures. The effect of initial enzyme concentration and pH on immobilization procedure were investigated and the change of Michaelis-Menten … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…On the other hand, Atay et al (2022) reported a slight decrease in the Km value from 5.55 mM to 5.05 mM and an approximately 1.8-fold increase in reaction velocity when immobilizing pig heart fumarase on poly(hydroxyethyl methacrylate) silanized with 3-mercaptopropyltriethoxysilane. In their approach, enzymes are immobilized on the carrier through a disulfide bond between the surface-positioned cysteine residues of the enzyme and the thiol groups of (3-mercaptopropyl) triethoxysilane.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…On the other hand, Atay et al (2022) reported a slight decrease in the Km value from 5.55 mM to 5.05 mM and an approximately 1.8-fold increase in reaction velocity when immobilizing pig heart fumarase on poly(hydroxyethyl methacrylate) silanized with 3-mercaptopropyltriethoxysilane. In their approach, enzymes are immobilized on the carrier through a disulfide bond between the surface-positioned cysteine residues of the enzyme and the thiol groups of (3-mercaptopropyl) triethoxysilane.…”
Section: Discussionmentioning
confidence: 97%
“…The binding of hydroxy groups on the carrier to areas close to the substrate binding site might interfere with access or binding of substrate to the substrate binding site, thereby leading to an increased Km value. However, although an increase in Km value was observed after immobilization, the lower Km value of immobilized CmFUM for fumarate compared to other immobilized fumarases suggests a superior affinity of immobilized CmFUM for fumarate (Atay et al, 2022;Giorno et al, 2001;Li et al, 2022;Marconi et al, 2001, Table 3). On the other hand, decrease in kcat was significant and was thought to be a major factor associated with the decrease in CmFUM activity following immobilization.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation